2001
DOI: 10.1088/0953-8984/13/49/301
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional electronic states at surfaces

Abstract: One-dimensional electron systems can now be synthesized at stepped surfaces by self-assembly of atomic and molecular chains. A wide variety of adsorbate and substrate combinations provides opportunities for systematically tailoring electronic properties, such as the intra-chain and inter-chain coupling, the electron count, magnetic moment and the Coulomb interaction. Angle-resolved photoemission with synchrotron radiation is an ideal probe to reveal the complete set of quantum numbers for electrons at an order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
95
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 92 publications
(144 reference statements)
1
95
0
Order By: Relevance
“…Already the flat Si͑111͒ surface breaks its threefold symmetry at submonolayer coverage and forms three domains of anisotropic n ϫ1 structures for many metals. 12 Furthermore, the use of stepped silicon 13 introduces an additional anisotropy at the surface that drives the formation of one-dimensional chain structures parallel to the step direction, which is ͓1 1 0͔ in our case. With gold atoms the ideal limit of a single chain per terrace can be achieved.…”
mentioning
confidence: 86%
“…Already the flat Si͑111͒ surface breaks its threefold symmetry at submonolayer coverage and forms three domains of anisotropic n ϫ1 structures for many metals. 12 Furthermore, the use of stepped silicon 13 introduces an additional anisotropy at the surface that drives the formation of one-dimensional chain structures parallel to the step direction, which is ͓1 1 0͔ in our case. With gold atoms the ideal limit of a single chain per terrace can be achieved.…”
mentioning
confidence: 86%
“…3,4 While a common approach to the study of such systems is to study atomic chains and wires on stepped and "furrowed surfaces," bulk crystals with quasi-one-dimensional chains also exist like the molybdenum and tungsten bronzes [5][6][7][8][9][10][11][12][13] and ͑TaSe 4 ͒ 2 I. [12][13][14] In 4 Se 3 is a semiconductor, unlike the quasione-dimensional conductors, and is thus not susceptible to change density wave effects 15 although the band structure should be highly anisotropic.…”
Section: Introductionmentioning
confidence: 99%
“…16 The In 4 Se 3 semiconductor crystal forms a layered structure characterized by, in principle, weak interaction of van der Waals type between the layers and strong covalent-ionic interactions within the layer, but the ͑001͒ surface is not "smooth." The quasi-two-dimensionality ͑2D͒ of layered crystals and, consequently, absence of free unsaturated electron bonds on the cleavage surfaces, do not quite apply here as the layers are not perfectly flat but corrugated, [16][17][18][19][20] resulting in quasi-one-dimensional chain structures at the semiconducting In 4 Se 3 ͑001͒ surface. In 4 Se 3 is, in fact, dominated by ͑In 3 ͒ 5+ multivalent clusters bonded with selenium through ionic covalent bonds.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The investigation of such systems is a very active research field that includes the theory of nucleation in 1D, [5][6][7][8][9][10] the investigation of atomistic diffusion [11][12][13][14][15][16][17] and epitaxial growth [1][2][3][18][19][20][21] in the presence of steps, the catalytic activity of step sites, 22 electron confinement in 1D states, [23][24][25][26] and the behavior of 1D magnetic materials. [27][28][29][30][31][32][33][34][35] Owing to the increase of binding energy at step sites, and depending on the substrate temperature, adatoms deposited on vicinal surfaces can self-assemble into chainlike structures by decorating the step edges.…”
Section: Introductionmentioning
confidence: 99%
“…1͑a͔͒, so that their length is ultimately determined by the density of defects along the step edges. Depending on the quality of the surface miscut and surface preparation, this density can be the order of 5 ϫ 10 −3 Å −1 on metal 2 and 6 ϫ 10 −5 Å −1 on Si 23 substrates. Scanning tunneling microscopy ͑STM͒ has shown that the formation of continuous monoatomic wires proceeds via the coalescence of increasingly long 1D islands that grow at the steps due to the diffusion of step-trapped adatoms.…”
Section: Introductionmentioning
confidence: 99%